Acute Lung Injury and Repair Scientific Fundamentals and Methods - Schnapp, Lynn M.; Feghali-Bostwick, Carol; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
Acute Respiratory Distress Syndrome (ARDS) remains an important cause of morbidity and mortality worldwide, and the incidence is predicted to increase with the aging population Several clinical disorders can initiate ARDS, including pneumonia, sepsis, gastric aspiration and trauma but despite intense research over the past 40 years, we still have an incomplete understanding of the pathophysiology of the disease and treatment remains largely supportive. This book provides an overview of acute lung injury and repair, describes current animal models to study lung injury and reviews current methodologies to study and measure lung injury and repair. Special emphasis is given to state of the art techniques and methods and relevance to human disease. Acute Lung Injury and Repair: Scientific Fundamentals and Methods is a useful resource for physicians and scientists who are interested in experimental model systems for insight into ARDS pathogenesis and treatment strategies.
Methods to Study Lung Injury and Repair -- Mouse Models of Acute Lung Injury -- Transgenic Animal Models in Lung Research -- Fundamental Methods for Analysis of Acute Lung Injury in Mice -- Invasive Measurement of Pulmonary Function in Mice -- Analysis of Epithelial Injury and Repair -- Flow Cytometric Evaluation of Acute Lung Injury and Repair -- Lung Imaging in Animal Models -- Genetic and Genomic Approaches to Acute Lung Injury -- MicroRNA Analysis in Acute Lung Injury.
Keywords: Medicine; Critical care medicine; Respiratory organs -- Diseases; Medicine & Public Health; Pneumology/Respiratory System; Intensive / Critical Care Medicine